CONTEOS CROMOSOMICOS EN PHILESIA MAGELLANICA J.F.GMEL. (LILIALES: PHILESIACEAE) - Jara-Seguel, Pedro; Fuentes-Ramírez, Andrés (Gayana Botánica, 2007)
Mitotic chromosome counts documented here for Philesia magellanica J.F.Gmel. (Philesiaceae) showed a diploid number 2n = 30 (x = 15), which is different to the numbers reported previously for the species. The 2n number of P. magellanica is similar to that documented previously for Lapageria rosea, which indicate a constancy of chromosome number within the family.